Revisiting search and review for work-based projects. Issue 5 (3rd September 2018) - Costley, Carol; Nottingham, Paula
ABSTRACT: The search and review of literature is a vital process for many higher education studies and often, an essential part of the research process. This paper focuses on the requirements of students based in the workplace who are doing work-based projects. Practitioner Researchers (PRs) use an iterative process that looks at the context and theories in use being explored as well as utilising expertise and professionally-generated materials in their field. This approach, discussed with academic and professional team members, favours a transdisciplinary structuring of knowledge that does not privilege academic sources but also recognises the importance of innovation based in the workplace. The authors argue that as more programmes are developing resources and strategies for PRs, there is a need to accommodate a redefined boundary for the search and review of literature, knowledge and information for higher education work-based research projects.